(untitled) (Informatica, 2024)
With the change of time, many famous buildings in history have evolved into objects that need to be protected, and the protection of architectural heritage is gradually paid attention to by people. Virtual reality technology has broad development prospects in industrial simulation, product display, architectural heritage protection and other aspects. Using virtual reality technology and intelligent robot to deal with the current architectural heritage protection problems, its advantages are: intelligent robot is a direct embodiment of the development of modern society; However, modern buildings are mostly wooden structures, which will accelerate the demise of buildings due to uncertain factors such as age, improper maintenance, technical limitations, tourist touch and corrosion of natural environment. In this context, this article through to the contemporary construction of multi-dimensional analysis, exploration and research, reference data, comparison and analysis of different types of digital preservation method, pointed out that the use of intelligent robot technology to save modern buildings, can not only reduce the man-made damage of existing buildings, and can effectively relieve damaged architectural heritage protection. VR technology can collect relevant information and maintain it, greatly reducing the damage caused by frequent visitors, while also allowing more viewers to watch without affecting residents. The audience can experience the difference between the virtual way and the personal experience, by thinking about the traditional digital expression way. Until today, some modern buildings still retain the breath of people’s life, those precious buildings are constantly seen by tourists, tourists touch, step on and take photos of the footprints will have an impact on themselves. In this paper, virtual reality technical data of indoor, outdoor and aerial photography are collected on site to show the dimensions, original appearance and details of architectural heritage as much as possible in the form of reverse model, which has relatively important historical significance and practical value.